Mapping the climate and agronomic digital advisory services landscape in West and Central Africa: A step towards making food systems productive and climate resilient - Manjari Singh; Mathieu Ouedraogo; Daniel Jimenez; Tiffany Talsma; Adama Ouedraogo; Desire Kagabo; Julian Ramirez; Peter Laderach (PLoS ONE, 2025)
This study explores and examines the availability of digital agricultural solutions (DAGs) to enhance agricultural resilience in the face of climate change. The countries under study—Burundi, Ivory coast, Democratic Republic of Congo (DRC), Ghana, Nigeria, and Rwanda—display varying levels of vulnerability, suffering from low adaptive capacity to address climate impacts. The study examines available DAGs to support farmers, including mobile-based platforms providing weather and agronomic advice, market information, and financial services. We highlight the diverse needs and challenges faced by three key user groups of digital agro-climatic services: farmers, service providers, and policymakers. All stakeholders require tailored approaches to improve adoption and impact. We employed a mixed-method approach that combined literature review with semi-structured interviews to identify existing digital solutions in agriculture. Next, we produced country-specific reports to assess the current state of agronomic digital advisory services, their users, and challenges. Ghana, Nigeria, and Rwanda have made notable strides in delivering these services, though challenges such as inadequate infrastructure, high internet costs, and gender disparities hinder their wider adoption. Additionally, data fragmentation and lack of harmonization across platforms pose significant barriers to optimizing these digital solutions. We discuss the role of public extension services and policy frameworks in fostering digital transformation in agriculture, with an emphasis on the need for better data harmonization to improve decision-making. The study underscores the importance of integrating digital technologies with stronger policies, improved infrastructure, and greater inclusivity to support climate-resilient agricultural practices in the region.